IMPLEMENTATION OF THE HERO WASTE APPLICATION TO INCREASE ENVIRONMENTAL AWARENESS OF MI AT-TAUFIQ STUDENTS IN THE MERDEKA CURRICULUM - Setiawan, Ricky; Jone P. Sodusta, Donne; Salsabila Firdausyi, Marsya; Zakia Zamania, Zeni; Novitasari, Kartika; Budi Amanda, Kartika; Octavia Arianto, Riska (EduStream: Jurnal Pendidikan Dasar, 2024)
The lack of action and deep understanding of waste management makes schools somewhat passive in addressing waste issues. This research aims to enhance environmental awareness by implementing a Project to Strengthen the Profile of Pancasila Students or Proyek Penguatan Profil Pelajar Pancasila (P5) with the integration of the Hero Waste application in managing waste in their life. The research was conducted at MI AT-Taufiq with 79 fourth-grade students as research subjects. The type of research used was classroom action research consisting of four stages: planning, implementation, observation, and reflection. Data were collected through observation and then analyzed using quantitative analysis techniques. The results of the study indicate that there was an increase in environmental awareness attitudes among students at MI AT-Taufiq. The calculation results of the N-Gain formula show an increase from cycle I to cycle II amounting to 0.45. The N-Gain value in the range of 0.3 ? g ? 0.7 is classified as moderate. This is indicated by students beginning to separate their waste into three categories: organic waste, inorganic waste, and residue, as well as taking action to recycle waste into artwork.